RANCANG BANGUN MINIATUR TURBIN ANGIN PEMBANGKIT LISTRIK UNTUK MEDIA PEMBELAJARAN - Ruzita Sumiati; Aidil Zamri (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2014)
Wind turbines convert the kinetic energy in wind into clean electricity. When the wind spins the wind turbine's blades, a rotor captures the kinetic energy of the wind and converts it into rotary motion to drive the generator. Wind electric systems are one of the most cost-effective home-based renewable energy systems with zero emissions and pollution. Many factors that influence the performance of wind turbines such as wind speed, blade shape, and number of blades. In Generator, Coil number of turn (N) also influence performance of wind turbine. Manufacture of wind turbine prototype as a learning medium to facilitate students in understanding the concept of wind electric system. Results of the test prototype wind turbine if the wind speed the greater the resulting voltage will be higher, the Coil number of turn (N) also affects the voltage generated.